Demanding Epistemic Democracy and Indirect Civics Pedagogy: The Performance-Oriented Music Ensemble - Pyrcz, Gregory E.; MacLean, Tessa Claire; Hopkins, Mark E. (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2017)
The participation of young adults in performance-oriented music ensembles can be seen to enhance democratic capacities and virtues. Much, however, turns on the particular conception of democracy at work. Although contemporary currents in music education tend towards models of liberal and participatory democracy to govern music ensembles, this essay contends that demanding epistemic democracy allows performance-oriented music ensembles the achievement of democratic virtues without sacrificing excellence as a central regulatory ideal. The inclusion of both men and women is shown to be particularly significant in this light. Central to its democratic epistemic ambition, the role of the conductor is considered in the last section of this article.